Demonstration of Direct Neurite-Osteoclastic Cell Communication In Vitro via the Adrenergic Receptor - Satoko Suga; Shigemi Goto; Akifumi Togari (Elsevier, 2010)
There is currently great interest in the bone metabolism induced by the sympathetic nerve system. Recently, direct neurite-osteoblastic cell communication was demonstrated using an in vitro co-culture model comprising neurite-sprouting murine superior cervical ganglia and MC3T3-E1 osteoblast-like cells. In the present study, we examined whether the direct nerve-osteoclastic cell communication was present in an in vitro co-culture model comprising cultured murine superior cervical ganglia and mouse osteoclast-like cells. RAW264.7 cells treated with receptor activator of NF-κ B ligand were used as osteoclast-like cells. We found that the addition of scorpion venom (SV) elicited neurite activation via intracellular Ca2+ mobilization and, after a lag period, osteoclastic Ca2+ mobilization in the co-culture. SV did not have any direct effect on the osteoclastic cells in the absence of the neurites. The addition of an α1-adrenergic receptor (AR) antagonist, prazosin, concentration-dependently prevented the osteoclastic activation that resulted as a consequence of neural activation by SV. We also found that α1-adrenergic receptor agonists evoked transient Ca2+ mobilization and gene expression of interleukin-6 in osteoclastic cells. These results demonstrate that osteoclastic activation occurs via α1-AR in osteoclastic cells as a direct response to neuronal activation. Keywords:: osteoclast, neurite, co-culture, cell communication, adrenergic receptor